FAKTOR-FAKTOR PENENTU YANG MEMPENGARUHI ADOPSI CLOUD COMPUTING DI INDONESIA - Setiawan, Sharen; Gui, Anderes (ISTEK WIDURI, 2023)
Today's technology is getting more and more advanced. Cloud Computing is one of the fastest growing technologies in Indonesia. Cloud Computing technology has developed in various business sectors from manufacturing companies to services. The purpose of making this paper is to answer the determining factors that have an impact on the company's decision to adopt Cloud Computing in Indonesia, using 2 approaches to the technology adoption literature. The survey conducted is a modification of the previous research which was distributed via google form, where the prospective respondents are those who work in companies in Indonesia from 12 September 2022 to 2 October 2022. There are 66 respondents who participated in this survey. The analysis uses SMART PLS3 software, which tests Conbarch Alpha, Outer Loading, Coefficient Path, Composite Reliability, Discriminant Validity. The results of this study show that compatibility, and complexity have a significant impact on perceived usefulness, top management support has a significant impact on perceived ease of use, and perceived ease of use has an impact on cloud computing adoption.